Amidoselenation and Amidotelluration of Alkenes using Oxygen as Terminal Oxidant. Issue 6 (22nd February 2017) - Sun, Kai; Wang, Xin; Zhang, Chong; Zhang, Saifei; Chen, Yao; Jiao, Hezhen; Du, Weimin
Abstract: A protocol has been established for oxygen‐mediated amidoselenation and amidotelluration of alkenes under mild conditions. This method provides a simple route to a series of structurally diverse β‐amido selenides and β‐amido tellurides in moderate to high yields. The wide substrate scope, good functional group tolerance, ease of large‐scale preparation and potential for product derivatization make this reaction attractive for the synthesis of nitrogen‐, selenium‐ and tellurium‐containing molecules. Abstract : It needs oxygen to survive : An oxygen‐mediated amidoselenation and amidotelluration of alkenes has been developed and a series of structurally diverse β‐amido‐selenides and β‐amido‐tellurides have been obtained under mild conditions.